2022
DOI: 10.3389/fcvm.2022.1005958
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of adherence of enhanced external counterpulsation in patients with coronary heart disease after discharge: A mixed-methods study

Abstract: BackgroundAlthough enhanced external counter pulsation (EECP) has been included in the cardiac rehabilitation prescription for coronary heart disease (CHD) in China, because the total treatment duration of a course of EECP is 36–36 h, the average hospital stay of CHD patients is short, and the adherence after discharge remains unclear. The purpose of this study is to investigate the adherence to EECP in CHD patients after discharge, and analyze the related influencing factors.MethodsA retrospective mixed metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…29,30 Our results showed that the level of education influenced early mobilization. Patients with higher education levels may have a deeper health knowledge 31 and a better understanding of the importance of early mobilization, thus promoting their motivation to get out of bed early. It has been hypothesized 32 that patients with low levels of education are more likely to have low knowledge mastery and low self-efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Our results showed that the level of education influenced early mobilization. Patients with higher education levels may have a deeper health knowledge 31 and a better understanding of the importance of early mobilization, thus promoting their motivation to get out of bed early. It has been hypothesized 32 that patients with low levels of education are more likely to have low knowledge mastery and low self-efficacy.…”
Section: Discussionmentioning
confidence: 99%